Death, 'deathlessness' and existenz in Karl Jaspers' philosophy - Peach, Filiz (Edinburgh University Press, 2008)
Filiz Peach provides a clear explanation of Jaspers philosophy of existence clarifying and reassessing the concept of death that is central to his thought